2012
DOI: 10.5009/gnl.2012.6.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Granulocyte/Monocyte Apheresis for the Maintenance of Remission in Patients with Ulcerative Colitis: A Prospective Randomized, Double Blind, Sham-Controlled Clinical Trial

Abstract: Background/AimsWeekly granulocyte/monocyte adsorption (GMA) to deplete elevated and activated leucocytes should serve as a non-pharmacological intervention to induce remission in patients with ulcerative colitis (UC). This trial assessed the efficacy of monthly GMA as a maintenance therapy to suppress UC relapse.MethodsThirty-three corticosteroid refractory patients with active UC received 10 weekly GMA sessions as a remission induction therapy. They were then randomized to receive one GMA session every 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Some studies [ 9 , 10 ] evaluated recently diagnosed UC patients with mild clinical activity, where GMA was associated with a good clinical response, but a not so profitable cost-benefit ratio. Consistent results have been drawn for GMA in the maintenance of remission [ 11 ]. Furthermore, other fields of application have been represented by subgroups where the safety profile is very important, such as adolescents [ 12 ], pregnant women [ 13 ], and patients with cytomegalovirus superinfection [ 14 ].…”
Section: Discussionsupporting
confidence: 83%
“…Some studies [ 9 , 10 ] evaluated recently diagnosed UC patients with mild clinical activity, where GMA was associated with a good clinical response, but a not so profitable cost-benefit ratio. Consistent results have been drawn for GMA in the maintenance of remission [ 11 ]. Furthermore, other fields of application have been represented by subgroups where the safety profile is very important, such as adolescents [ 12 ], pregnant women [ 13 ], and patients with cytomegalovirus superinfection [ 14 ].…”
Section: Discussionsupporting
confidence: 83%
“…Efficacy of CAP for maintenance of remission in UC has been reported [ 134 ], although its evidence level is low and its use has not yet been approved for this purpose. There is only one case report suggesting its efficacy for maintaining remission in CD [ 135 ].…”
Section: Therapeutic Interventions For Ibdmentioning
confidence: 99%
“…40% in the GMA arm avoided relapse in comparison to 9.1% and 18.2% in the sham and control arm, respectively. Although no significant values were obtained the study concluded that GMA potentially might prevent UC relapse when used as a maintenance therapy .…”
Section: Discussionmentioning
confidence: 68%